Synthesis of reduced graphene oxide by using palm oil mill effluent (POME) - Ban Kiat, Tey (2015)
The increase of world palm oil demand has driven a significant increase in palm oil production. Indirectly, palm oil mill effluent (POME) production also has increased drastically. In the material science field, graphene is a marvellous material due to its high specific surface area (theoretically 2630 m2/g for single-layer graphene), extraordinary electronic properties and electron transport capabilities, unprecedented pliability, strong mechanical strength and excellent thermal and electrical conductivities. The abundance β-carotene (strong reducing agent) found in POME can be utilized to synthesize graphene. β-carotene can be used for reduction of graphene oxide instead of hydrazine as this approach is more environmentally friendly. The objectives are to reduce graphene oxide by using β-carotene extracted from POME, optimise the β-carotene concentration to reduce graphene oxide and analyse reduced graphene oxide using Ultraviolet-visible Absorption Spectrophotometry (UV-Vis), Fourier Transform Infrared (FTIR) and cyclic voltammetry (CV). Fabrication of graphene oxide, extraction of β-carotene, and reduced of graphene oxide by β-carotene will be covered in this research. Firstly, the pre-oxidation step was carried out to help to achieve a higher degree of oxidation. Subsequently, the graphite was oxidized by potassium permanganate and undergoes ultrasonication to produce graphene oxide. After that, β-carotene was extracted from POME by using soxhlet extraction. Graphene oxide was reduced by extracted β-carotene from POME and un-treat POME. 4mM of extracted β-carotene was illustrated a successfully reduced result monitored by UV-Vis and FTIR. Quantification of reduced graphene oxide treats by extracted β-carotene from POME has been monitored by using UV-Vis and the peak detected will be shifted from 230 nm to 270 nm. For FTIR analysis, the oxygen associated intensities bands were reduced, such as 3400 cm-1 (for hydroxyl stretching) was completely disappeared in the CrGO spectrum. Besides that, cyclic voltammograms of several types of rGO by applying in the sensor field also have been monitored.